Restoration of Boundary Markers and the Determination of Boundary Points ‑ Proposed Amendments to the Laws of Poland - Maślanka, Józef (Geomatics and Environmental Engineering, 2020)
The article presents proposed amendments to the provisions of the Polish Geodetic and Cartographic Law regarding the restoration of boundary markers and the determination of boundary points of cadastral parcels. The current legal regulations are both insufficient and ambiguous, which results in significant and harmful discrepancies both in the interpretation of the legislation and its application. As a result, the database of the register of land and buildings (EGiB), which keeps the records on the boundaries of cadastral parcels and the attributes of boundary points describing these boundaries, frequently does not correspond to the actual status and is therefore unreliable. Due to the importance of this data, and of the entire EGiB database, to the socio-economic system of the country, this should no longer be tolerated. In this research paper, the author highlights the problems both relating to the legal regulations on the procedure as well as to the content of the database of the register of land and buildings. In both cases, the defects carry consequences that are adverse for the quality of the EGiB data and contribute to the loss of their reliability The specific amendments to the legislation proposed in this article are to prevent the further misinterpretation and misapplication of the current legal provisions and should allow to meet the reasonable expectations and needs of the users of the data contained in the register of land and buildings, especially property owners.